Merlin: metabolic models reconstruction using genome-scale information - Dias, Oscar (2010)
This article describes Merlin, a user-friendly program that performs functional genomic annotations of lists of genes. Merlin retrieves information of each homologue and automatically scores the results, allowing the user to change the score selection, and dynamically (re-)annotate the genome. Merlin expedites the transition from genome-scale data to SBML metabolic models, allowing the user to have a preliminary view of the biochemical network.